EDUCATIONAL COMMUNICATION FROM THE PERSPECTIVE OF PROPHET MUHAMMAD SAW (A STUDY OF AS-SIRAH AN-NABAWIYAH BY ALI MUHAMMAD ASH-SHALLABI) - Zega, Intan Permata Sari; Arsyad, Junaidi; Hanum OK, Azizah (Pena Cendekia Insani, 2025)
This study examines the educational communication strategies of Prophet Muhammad SAW as presented in As-Sirah An-Nabawiyah by Ali Muhammad Ash-Shallabi, in response to the degradation of values in contemporary Islamic education. The purpose of this research is to reconstruct a prophetic educational communication model that is relevant to the challenges of the present era. The method employed is descriptive qualitative with a library research approach, utilizing primary sources and content analysis. Data were derived from historical narratives of the Prophet’s educational practices across various social contexts. The findings reveal that the Prophet’s educational communication is transcendental, humanistic, and emancipatory in nature, and proven to be effective in shaping Islamic character. These findings recommend the reinforcement of prophetic communication values within the curriculum and praxis of modern Islamic education.